Self-Control and Juvenile Delinquency in Jambi Boarding School Environment: A Correlational Study - Tiara Putri Lars; Rion Nofrianda; Beny Rahim (Yayasan Adra Karima Hubbi, 2025)
Juvenile delinquency is a form of deviant behavior that is still often found in educational environments, including in boarding schools, which should play a role in character building and self-control of students. This study aims to examine the relationship between self-control and juvenile delinquency in students of SMA X Boarding School in Jambi. The study used a quantitative correlational approach involving 81 students in grades XI and XII who were selected using a purposive sampling technique. The instruments used consisted of a Self-Control Scale compiled based on Averill's theory (1973) and a Juvenile Delinquency Scale based on Jensen's theory (1985). Data analysis was performed using the Pearson Product Moment correlation technique through the SPSS version 25 program. The results showed a significant negative relationship between self-control and juvenile delinquency (r = ?0.520; p = 0.001) with an effective contribution of 27% (R² = 0.27). This finding indicates that the higher the students' self-control, the lower the tendency for juvenile delinquency. This study emphasizes the importance of strengthening self-control among adolescents through ongoing character development and counseling programs.